THE EFFECT OF REPLACEMENT OF LIQUID ORGANIC FERTILIZER OF GOAT DRUGS WITH CORN WASTE AT VARIOUS DOSAGES ON GROWTH AND PRODUCTION OF GREEN Asystasia gangetica - A. T., Mukti; Duarsa, M. A. P.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of replacing liquid organic fertilizer from goat manure with corn waste at various doses on the growth and yield of Asystasia gangetica forage. The research has been carried out at the Greenhouse, on Jalan Raya Sading Number: 93, Mengwi District, Badung Regency, Bali. This study lasted for four months, data collection using a Completely Randomized Split-Plot Design with two factors. The main plot is the replacement of liquid goat manure consisting of goat manure + water (KK1), goat manure + EM4 + water (KK2), and goat manure + EM4 + corn waste + water (KK3) and the subplot is the dose of goat manure liquid fertilizer consisting of 0 l ha -1 (D0), 5,000 l ha -1 (D1), 10,000 l ha -1 (D2), 15,000 l ha -1 (D3). There were 12 treatment combinations and repeated four times so that there were 48 experimental pots. The variables observed were growth variables, forage yields and characteristics of Asystasia gangetica . There was no interaction between fertilizer replacement and fertilizer dosage on growth and forage yields. The results of this study indicate that the application of goat manure + EM4 + corn waste + water (KK3) tends to give the best growth and yield of Asystasia gangetica compared to goat manure + water (KK1) and goat manure + EM4 + water (KK2). The fertilizer dose of 5,000 l ha -1 (D1) tends to give the best growth compared to doses of 0 l ha -1 (D0), 10,000 l ha -1 (D2) and 15,000 l ha -1 (D3). From this research, it can be concluded that corn waste can replace goat manure by 50% for the growth and yield of Asystasia gangetica . Keywords: type of fertilizer, dose of fertilizer, Asystasia gangetica, growth, yield